Role of Rhizospheric Bacillus megaterium HGS7 in Maintaining Mulberry Growth Under Extremely Abiotic Stress in Hydro-Fluctuation Belt of Three Gorges Reservoir - Ou, Ting; Zhang, Meng; Huang, Yazhou; Wang, Li; Wang, Fei; Wang, Ruolin; Liu, Xiaojiao; Zhou, Zeyang; Xie, Jie; Xiang, Zhonghuai (Frontiers in Plant Science, 2022)
Plant growth promoting rhizobacteria have been shown to play important roles in maintaining host fitness under periods of abiotic stress, and yet their effect on mulberry trees which regularly suffer drought after flooding in the hydro-fluctuation belt of the Three Gorges Reservoir Region in China remains largely uncharacterized. In the present study, 74 bacterial isolates were obtained from the rhizosphere soil of mulberry after drought stress, including 12 phosphate-solubilizing and 10 indole-3-acetic-acid-producing isolates. Bacillus megaterium HGS7 was identified for further study due to the abundance of traits that might benefit plants. Genomic analysis revealed that strain HGS7 possessed multiple genes that contribute to plant growth promotion, stress tolerance enhancement, and antimicrobial compounds production. B. megaterium HGS7 consistently exhibited antagonistic activity against phytopathogens and strong tolerance to abiotic stress in vitro. Moreover, this strain stimulated mulberry seed germination and seedling growth. It may induce the production of proline and antioxidant enzymes in mulberry to enhance drought tolerance and accelerate the growth recovery after drought stress. The knowledge of the interactions between rhizobacteria HGS7 and its host plant might provide a potential strategy to enhance the drought tolerance of mulberry in a hydro-fluctuation belt.